The lived reality and meaning of Lean Thinking for nurses and nursing at an NHS Hospitals Trust - Field-Richards, Sarah Elizabeth (2017)
Lean Thinking (Lean) is a management philosophy originating from the Toyota automobile manufacturing company in Japan. Lean has been widely adopted in the United Kingdom (UK) National Health Service (NHS) as a panacea for addressing challenges that threaten its sustainability. Attempts to evaluate the outcomes of Lean implementation, in order to assess its claims to improve efficiency, quality and safety, have proved challenging owing to ambiguity surrounding the definition of Lean, differences in approaches to, and the poor quality of literature reporting, implementation. Lean continues to be adopted in healthcare regardless however, and a body of literature considering the consequences of Lean more broadly, is suggestive of implementation holding other, far-reaching implications.